A Development of Realistic Mathematics Learning Tools to Improve Students' Mathematical Literacy Ability - Riky Prasetia Wijaya; Mega Teguh Budiarto; Pradnyo Wijayanti (MEJ (Mathematics Education Journal), 2021)
The purpose of this research to: (1) describe the development process and produce realistic mathematics learning tools that are good for improving students 'mathematical literacy, (2) describe the effectiveness of realistic mathematics learning to improve students' mathematical literacy. The research population was class X students of seniour high school 3 Surabaya in the 2020/2021 academic year and teachers who teach mathematics in that class. The following conclusions were obtained: (1) The process of developing realistic mathematics learning tools using the PLOMP development model (2010) and the results of developing realistic mathematics learning tools for the matter system linear equation three variables (SPLTV) using the Ploom development model resulted in learning tools (RPP, LKS, and TLM) qualify the criteria of good quality equipment. (2) Based on the results of descriptive analysis in the implementation class, it was found that realistic mathematics learning was effective in improving students' Mathematical Literacy.